THE ROLE OF MEDIA IN GENDER VIOLENCE, HUMAN RIGHT AND PEACE BUILDING - Riak , Dr Gabriel Alier; Ayuel , Dut Bol (IJRDO - Journal of Social Science and Humanities Research, 2022)
The chapter introduces the study, with background that highlight on the key variable and purpose of the study. Problem Statement, The objectives and research questions are given as a stream line to the nature of the study carried out by the researcher. The scope of the study, conceptual frame work and significance of the study are presented and discussed.